Restorative justice and its reflections in the administration of justice under Nigerian customary law (2016)
The quest for justice is a basic human attribute from time immemorial. British colonization and its adversarial system of justice, met the administration of customary law which served the purpose of justice in Nigeria from time immemorial, characterized by community participation, flexibility, absence of rigid procedure and technicalities, speedy dispensation of justice and absence of courts in the English fashion, but efficient and trusted by the people it bound. Restorative justice is a theory of justice that emphasizes repairing the harm caused by criminal behavior through stakeholder-driven cooperative processes that bring all willing stakeholders to meet to resolve their differences. This article argued that restorative justice is not new to Nigeria as it reflects attributes of the Nigerian customary law. There are common attributes shared by both systems, including participation of the offender, offended and the community, non-adversary resolution of conflict, focus on repair and restoration of peace rather than punishment, technicalities recognition of the victim of crime rather than the state as a principal party. It recommended better dispensation of justice in Nigeria through leveraging on the common attributes shared by the administration of customary law and restorative justice.